Characteristics of relationships, types and strategies in a Brazilian cluster. Issue 4 (11th April 2016) - Tristão, Hélcio Martins; Oprime, Pedro Carlos; Pimenta, Márcio Lopes
Abstract : Purpose: – The purpose of this paper is to contribute to the theoretical development of the theme by the proposition of an industrial cluster typology method considering that the set of local variables related to the firms characteristics are essential for the strengthening of the interfirms' relationship and consequently their performance. Design/methodology/approach: – The theoretical basis of this study are the types of clusters found in literature and the research. A survey with several types of actors were performed with companies from footwear production chain in the region of Franca, Brazil. Data were analyzed through descriptive statistics techniques as well as multivariate exploratory methods. Findings: – This study highlight multiple characteristics derived from different cluster typologies within the same productive chain. Originality/value: – From a theoretical standpoint, the research results extended the perspective about the strategic role played by the local cooperation and also offer to managers and representative institutions a possibility to reflect on different types of governance principles adopted in collective actions.